Social Forestry in Tamil Nadu - Wilson, J. (Indian Forester, 1979)
Afforestation of Government lands outside the Reserved Forests under the Farm Forestry Programme was taken up in the State of Tamil Nadu from 1960 onwards. The areas chosen are mainly foreshores of the large number of tanks in the state. Some planting has been done on barren hillocks as well. The scheme has been sucessful and extensive areas have been planted. The revenue obtained by the sale of the plantations raised is shared by the Government and the panchayats concerned on a fifty-fifty basis. Apart from increasing revenues, the scheme has brought in a number of direct and indirect benefits to the people. The Farm Forestry scheme is now part of the larger Social Forestry Programme, which has been introduced pursuant to the recommendations of the National Commission on Agriculture. Three new forest divisions have been constituted exclusively for Social Forestry, thereby facilitating a larger coverage of areas. Other aspects of Social Forestry such as planting of road side avenues and sale of seedlings to the public for planting on private lands have also been taken up. There is immense scope for these items of work and the benefits that are likely to accrue to the community are great. It is hoped that a separate forest division for Social Forestry could be established in each of the 13 districts of the state, so that the people may derive the full benefits of this laudable programme.